Surveillance data Early Warning Alert and Response System (EWARS) as information for decision making in Wonogiri District, Central Province, 2017 - Menikha Maulida; Suprio Heryanto; Trisno Agung Wibowo (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
EWARS was developed to conduct surveillance in outbreak detection and response. EWARS officers in Wonogiri District collected data but do not process it. Data must be processed to become information in decision making. This study aimed to evaluate the system of data processing and analysis system in EWARS as information for decision making.The design study used is descriptive. Subjects in this study were 25 of 34 Public Health Center (PHC) EWARS surveillance officers and 1 district surveillance manager. Evaluation conducted at PHC in December 2017-January 2018. Sample size of PHC surveillance officers was calculated using Slovin formula. Primary data were obtained by interview using structured questionnaire and observation. Secondary data were obtained from EWARS data. Data analysis was done descriptively.There were 3 of 25 PHC officers who have done data analysis but not yet appropriate. 1 of them do manual analysis on notebooks, 2 others do the analysis made by others. 25 EWARS surveillance officers have never received any data analysis training. EWARS system cannot detect outbreak. EWARS data has never been used to program design. Dissemination of EWARS data has never been done. EWARS surveillance data cannot be used as information for decision-making at the PHC level because officers have not done the processing and data analysis, and dissemination has never been done. Data analysis training should be conducted and dissemination of data on a regular basic with bulletins or monthly meetings.